Institutional Expansion and Scientific Development in the Periphery: The Structural Heterogeneity of Argentina’s Academic Field - Beigel, Maria Fernanda (2018)
The relationship between “marginal” and “mainstream” science has, in recent decades, become a matter of discussion. Traditional perspectives must be reexamined in the wake of transformations in the international circulation of knowledge and the subsequent diversification of scientific “peripherality”. Argentina represents an interesting case with which to explore the structure of “peripheral centres” and new forms of scientific development. While it has recently experienced an expansion in terms of institutionalization, professionalization, and internationalization, that process has been coupled with entrenchment of existing institutional asymmetries and persistent intra-national inequalities; academic prestige is distributed according to opposite principles of legitimation (local/international). Our main task is to explore the current state of research capacities pursuant to that expansion in order to analyze the diverse styles in which knowledge is produced. In our analysis, we make critical use of Bourdieu’s concept of field and the Latin American category of “structural heterogeneity,” while also focusing on the question of circulation. The paper outlines how professionalization has developed locally over time, and the historical tension between the National Council for Scientific and Technical Research and the public universities. It describes the current structure of the scientific field in terms of researchers, institutes, publishing circuits, and institutional evaluative cultures. It focuses on geographical asymmetries in order to assess the distribution of new human and material resources throughout the country. Finally, it addresses the current situation under the new government, and raises concern over recent regressive actions.